Teknik Budidaya Tanaman Talas (Colocasia esculenta Scho) sebagai Upaya Peningkatan Hasil Produksi Talas Di Desa Situgede - Haifa Azzahra; Yola Difa Mora Lubis; Sandra Dewi Hartanti; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Taro is the main commodity in Situgede Village with Taiwanese taro and bentul taro varieties. The farmers are more focused on developing Taiwan taro because Taiwan taro is more tolerant of pest and disease attacks even though for the quality of bentul taro are superior. The current problems is In the agricultural process carried out by farmers in the village of Situgede during the planting period until the taro harvest there is no cultivation that is carried out specifically, so that the yield obtained is not optimal. It is necessary to do taro cultivation techniques and special attention related to planting spacing, intercropping, and extermination of existing pests to increase the value of taro production in Situgede Village. This study aims to find out how to cultivate Bogor taro plants in Situgede Village, Bogor Regency, West Java. And to find out the process of taro farming in Bogor in Situgede Village, Bogor, West Java. The methods used were observation, interviews, and observations through direct participation (SUIJI SLP 2019 program) in the community in the village of Situgede. The results obtained from this study are the main pests that attack taro plants in Situgede village are grasshoppers (Oxya sp.) which cause symptoms in the form of hollow leaves. Key words: Cultivation of taro, intercropping, plant disturbing organisms